Pengaruh Kompensasi, Kepemimpinan dan Pengawasan Terhadap Kedisiplinan Kerja Karyawan - Karina Oktavia Barus; Veny Puspita; Sintia Safrianti (Journal of Trends Economics and Accounting Research, 2023)
This study aims to determine how much influence compensation, leadership and supervision have on the work discipline of employees of PT. Nareco Lestari Bengkulu City. The population in this study were 35 employees where the sample totaled 35 employees obtained through the sampling technique with saturated sampling technique. The method of analysis of this research is a quantitative method using the IBM SPSS 21 software tool. From the results of the study it can be concluded that the results of the t test on X1 (compensation) have a significant value = 0.338 greater than significant = 0.05 this means that H0 is accepted and Ha is rejected, which means that the compensation variable does not have a partial effect on work discipline (Y). The results of the t test on X2 (leadership) have a significant value = 0.402 greater than significant = 0.05, this means that H0 is accepted and Ha is rejected, which means that the leadership variable has no partial effect on work discipline (Y). The results of the t test at X3 (supervision) have a significant value = 0.000 less than significant = 0.05. This means that H0 is rejected and Ha is accepted, which means that the supervision variable has a partial effect on work discipline (Y). Simultaneously, compensation, leadership and supervision affect the work discipline of employees of PT. Nareco Lestari Bengkulu City.